Kajian Regulasi Upaya Pemerintah Dalam Memajukan Kesejahteraan Masyarakat Melalui Reformasi Sektor Keuangan Menurut Undang-Undang Nomor 4 Tahun 2023 Tentang Pengembangan dan Penguatan Sektor Keuangan (UU P2SK) - Mukti, Idul; Jadidah, Fikrotul (Postulat, 2025)
Financial sector reform in Indonesia through Law Number 4 of 2023 concerning the Development and Strengthening of the Financial Sector (UU P2SK) is a strategic step by the government to improve public welfare by strengthening financial inclusion, economic stability, and stricter supervision of the financial sector. This study uses a type of normative legal research, namely legal research that focuses on norms or rules in applicable laws and regulations. The approaches used are the statute approach and the conceptual approach. This regulation aims to strengthen the role of the Financial Services Authority (OJK) in maintaining the stability of the financial system and creating a more inclusive and transparent financial climate. A case study in Aceh Province highlights the positive impact of the P2SK Law, but factors such as infrastructure and financial literacy influence its implementation. One of the main focuses of the P2SK Law is stricter regulation of financial institutions, including the rapidly growing fintech sector, in order to protect consumers and prevent practices that are detrimental to society. Through the P2SK Law, it is hoped that the financial sector can have a positive impact on the economy, especially in terms of empowering MSMEs and creating new jobs. In addition, this regulation also focuses on environmental sustainability by strengthening the green finance sector, which encourages financing for environmentally friendly projects such as renewable energy and waste management. However, a major challenge in implementing the P2SK Law is the low level of financial literacy in Indonesia which hinders the achievement of optimal financial inclusion. Therefore, it is important for the government to strengthen financial education programs at all levels of society. In this context, the success of financial sector reform is highly dependent on the synergy between the central and regional governments, as well as public support in understanding and accessing available financial services. In addition, the P2SK Law is expected to create a more transparent, accountable, and sustainable financial system, so that it can improve people's welfare evenly. With comprehensive regulatory strengthening and proper implementation, it is hoped that the Indonesian financial sector can support inclusive and sustainable economic growth for all levels of society.